Forensic Aspects of Perinatal Deaths - Cohen, Marta C. (Acad Forensic Pathol, 2018)
From a forensic pathologist’s perspective, there are several aspects of the perinatal postmortem that are particularly important. If a fetus is found abandoned, the pathologist needs to ascertain the fetal age, the appropriateness of growth, if the baby was born alive or dead, and the possible causes of death. In cases of litigation for perinatal deaths occurring in hospitals, access to the obstetric and neonatal notes (if the baby is born alive and dies a few hours or days later) is fundamental to reach a correct interpretation and conclusion. The most important points to consider in cases of intrapartum death are the roles of asphyxia and trauma in the causation of the baby’s death. Timing of the fetal death in relation to delivery may also be an important point in these cases. Finally, intrapartum lesions should always be considered in the differential diagnosis of possible child abuse in babies aged two months or less.